UTICAJ TRENINGA SA AKCENTOM NA SNAGU I BRZINU NA RAZVOJ TIH SPOSOBNOSTI KOD TRENIRANIH I NETRENIRANIH DJEČAKA (STARIH 12 GODINA) - Siniša Srdić (University of Banja Luka, Faculty of physical education and sport, 2010)
The key factor in preparation of the optimal training programme is a comprehensive research inthe field of the strength and the speed motory dimensions. Rationally chosen means and the modalities with an adequete intenisity and burden capacity enable even development of these motory capabilities.The main goal of the research, applying variables for determination of motory dimensions of the strength and the speed, was to spot the distinctions between trained and untrained twelve year sold boys. Two measurements were conducted, the initial one that lasted for 6 weeks and conducted before the implementation for the training model, and another, the final one,conducted after the implementation of the training model. Analysis of the values that are result of the application of the statistic method, shows that in both measurements better results were shown with the trained boys, whereas the training model had partly positive effect on the efficiency of the tests conducted to measure the strength and the speed at both groups.